2012
DOI: 10.1007/978-3-642-33489-4_19
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Private and Public Sector on Information Systems Development and Maintenance Efficiency

Abstract: Abstract. This paper provides a comparison between public and private organizations on key figures relative to the information systems support activities. Many have claimed that public sector has a less satisfactory conduct of information system support than private sector. In this article we present selected data from survey investigations performed among Norwegian organizations on how they conduct information systems development and maintenance. This investigation has earlier been compared with similar inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
(30 reference statements)
1
1
0
Order By: Relevance
“…Two exceptions, both in the nancial sector, are the Financial Supervisory Authority and the National Government Employee Pensions Board -two anomalies that constitute interesting directions for future work. Nevertheless, our results con rm the conclusion by Krogstie [19], i.e., so ware development in the public appears as mature as in the private sector.…”
Section: So Ware Engineering Best Practices (Rq3)supporting
confidence: 89%
See 1 more Smart Citation
“…Two exceptions, both in the nancial sector, are the Financial Supervisory Authority and the National Government Employee Pensions Board -two anomalies that constitute interesting directions for future work. Nevertheless, our results con rm the conclusion by Krogstie [19], i.e., so ware development in the public appears as mature as in the private sector.…”
Section: So Ware Engineering Best Practices (Rq3)supporting
confidence: 89%
“…Some research claims that public sector projects tend to be poorly conducted compared to its private sector counterparts [16]. On the other hand, in a study conducted in Norway in 2012, a number of project indicators were compared between public and private organizations, and the authors found no signi cant di erences [19]. Nonetheless, there are indeed contextual di erences between soware projects in the public and private sectors.…”
Section: So Ware Engineering In the Public Sectormentioning
confidence: 99%